2017
DOI: 10.1007/s10661-017-6288-5
|View full text |Cite
|
Sign up to set email alerts
|

Dental fluorosis, nutritional status, kidney damage, and thyroid function along with bone metabolic indicators in school-going children living in fluoride-affected hilly areas of Doda district, Jammu and Kashmir, India

Abstract: A case-control study was undertaken among the school children aged 8-15 years to know the presence and severity of dental fluorosis, nutrition and kidney status, and thyroid function along with bone metabolic indicators in Doda district situated at high altitude where drinking water was contaminated and heat stress. This study included 824 participants with an age of 8-15 years. The results of the study reviled that dental fluorosis was significantly higher in affected than control area children. Urinary fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The transfer of chemicals from the subcomponents of the food chain to the upper constituents imparts a risk to the ecosystem as the chemicals tend to accumulate and can be transferred from one food chain to another [3]. The concentration of bioaccumulated heavy metals in the fish body is a function of some environmental parameters, including pH, temperature, alkalinity of the environment, pollutant type, sampling site [4, 5]. The presence of heavy metals in marine environment is the results of two main sources of contamination: natural occurring deposit and anthropogenic activities such as.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of chemicals from the subcomponents of the food chain to the upper constituents imparts a risk to the ecosystem as the chemicals tend to accumulate and can be transferred from one food chain to another [3]. The concentration of bioaccumulated heavy metals in the fish body is a function of some environmental parameters, including pH, temperature, alkalinity of the environment, pollutant type, sampling site [4, 5]. The presence of heavy metals in marine environment is the results of two main sources of contamination: natural occurring deposit and anthropogenic activities such as.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of heavy metals in marine environment is the results of two main sources of contamination: natural occurring deposit and anthropogenic activities such as. domestic, industrial, and agricultural activities [4, 6].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between dental health and demographic factors such as age, gender, place of residence, or unfavorable oral health care, as well as unhealthy lifestyles, are well-documented in literature. [54555657]…”
Section: Discussionmentioning
confidence: 99%
“…From the results, they concluded that in comparison to the controls, children living in the fluoride endemic areas are more severely affected with altered thyroid and metabolic functions. 14 Yun et al investigated the current incidence of endemic fluorosis in the floodplain area. For carrying out the epidemiological survey of endemic fluorosis, they surveyed 16 countries.…”
Section: Discussionmentioning
confidence: 99%